Analisis Ph Dan Kadar Nitrogen Total Menggunakan Metode Kjeldah Pada Pupuk Organik Padat - Setyaningrum, Dyah; Kasanah, Uswatun (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2024)
This study aims to measure the pH and nitrogen content in fertilizer samples at Balai Pengkajian Teknologi Pertanian in Semarang. measurements based on the Standar Nasional Indonesia (SNI) 19-7030-2004. Analysis of the pH of the fertilizer sample using electrometric method. While the nitrogen content of the samples was carried out using the Kjeldahl method which went through three stages, namely the destruction process, the distillation process and the titration stage. The results of the analysis showed that the pH of the sample was 7.34 with a nitrogen content of 1.00481. Based on these data, the fertilizer samples comply with SNI 19-7030-2004.